(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
ABSTRACT AIMS & OBJECTIVES The study was conducted to compare the effect of • Bupivacaine Heavy 0.5% 3 ml with fentanyl (25 mcg) 0.5 ml. • Bupivacaine Heavy 0.5% 3 ml with Butorphanol (25 mcg) 0.5 ml When administered intrathecally for lower limb orthopedic procedures. MATERIAL AND METHODS After obtaining a written and informed consent a comparative study of 60 patients. Patients were randomly divided in two groups of 30 each. Group BB (Butorphanol group) received 25 mcg Butorphanol with 15 mg hyperbaric Bupivacaine (0.5%; 3.0 ml) Group BF (Fentanyl Group) received 25 mcg fentanyl with 15 mg hyperbaric Bupivacaine (0.5%, 3.0 ml). BACKGROUND • Amongst the drugs used for spinal anesthesia Bupivacaine is still considered as the standard drug. Combining opioids with local anesthetics has got a synergestic effect, improving intra & postoperative analgesia. Combination of these agents reduces side effects caused by either of them. • We therefore conducted this study to evaluate the efficacy of Butorphanol & Fentanyl as adjuvant to Bupivacaine in lower limb orthopedic surgeries. OBSERVATION AND RESULTS • When Fentanyl and Butorphanol are used as an adjuvant to hyperbaric Bupivacaine for spinal anesthesia, Butorphanol provides longer duration of sensory & motor block compared to Fentanyl. • Duration of analgesia was also longer with Butorphanol which delayed the time for 1st analgesic request compared to fentanyl. • No significant haemodynamic changes or adverse effects were noted with either adjuvant. CONCLUSION Though Butorphanol intrathecally did not enhance the degree of sensory or motor block, its prolonged duration of Bupivacaine induced sensory block & reduced analgesic requirement during early post op period, with good hemodynamic stability without any adverse effects.